Mechanochromic MOF nanoplates: spatial molecular isolation of light-emitting guests in a sodalite framework structure - Chaudhari, A; Tan, J (Royal Society of Chemistry, 2018)
Mechanochromic materials have a wide range of promising technological applications, such as photonics based sensors and smart optoelectronics. Examples of mechanochromic metal-organic framework (MOF) materials, however, are still relatively uncommon in the literature. Herein, we present a previously undescribed Guest@MOF system, comprising “Perylene@ZIF 8” nanoplates which will undergo a reversible 442 nm ⇌ 502 nm photoemission switching subject to a moderate level of mechanically-induced pressure at tens of MPa. The nanoplates were constructed via high-concentration reaction (HCR) strategy at ambient conditions, to yield a crystalline ZIF-8 framework hosting the luminous Perylene guests; the latter confined within the porous sodalite cages of ZIF-8. Remarkably, we show that in a solid-state condition, it is the spatial isolation and nano-partitioning of the luminescent guests that bestow a unique solution-like optical properties measured in the host-guest assembly. As such, we demonstrate that switchable red- or blue-shifts of the visible emission can be accomplished by mechanically modifying the nanoscale packing of the nanoplates (e.g. monoliths, pellets). Theoretical calculations suggest that the elasticity of the host’s sodalite cage coupled with the intermolecular weak interactions of the confined guest are responsible for the unique mechanochromic luminescence behavior observed.